Development of a Game Based Volleyball Learning Model at Sungai Kakap 21 State Elementary School - Sulistya Megawati; Muhammad Suhairi; Suriani Sari (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This study aims to develop an effective game-based volleyball learning model at Sungai Kakap 21 state elementary school. The research method used is development research. The stages of the research include needs analysis, designing learning models, implementing learning models, and evaluating the effectiveness of learning models. Literature study and field observations were conducted to identify students' needs and learning conditions at Sungai Kakap 21 state elementary school. The learning model is designed by considering the elementary school curriculum and learning principles that are appropriate to child development. The implementation of the learning model is carried out through sports learning sessions involving grade 4 students. Relevant data is collected during implementation to evaluate the effectiveness of this learning model. The results showed that this game-based volleyball learning model was effective in increasing student interest and participation, as well as technical and tactical skills in volleyball. This research makes an important contribution to the development of innovative and fun sports learning models in elementary schools.